PENGEMBANGAN-GAME EDUKASI-BERBASIS WEBTOOL BAAMBOOZLE PADA MATERI-SISTEM PEREDARAN DARAH-MANUSIA - Hilmizein, Roif; Setiadi, Anandita Eka; Qurbaniah, Mahwar (BIOEDUKASI (Jurnal Pendidikan Biologi), 2025)
Teacher interviews revealed a lack of student enthusiasm during lessons, particularly on the topic of the human circulatory system. The media commonly used—student worksheets (LKPD) and textbooks—were considered somewhat helpful but insufficiently engaging due to their monotonous nature. Teachers also expressed the need for electronic learning media to diversify instructional methods. In response, this study developed an educational game using the Baamboozle webtool, selected for its ease of use and interactivity. The objectives of this study were to evaluate the validity of the educational game and assess student responses to its use. A Research and Development (R&D) approach was employed, following the Research-Development-Research (R-D-R) model. Data were collected through expert validation and student response questionnaires. Validation results showed high levels of validity across media design (98.18%), content (93.33%), and language (88%), all categorized as “very valid.” Student responses were also highly positive, with an average score of 92.47%. These findings indicate that the Baamboozle webtool-based educational game on the human circulatory system is highly valid and well-received by students, suggesting its effectiveness as a digital learning medium.